2017
DOI: 10.1093/jee/tox174
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth of Dysaphis pyri (Hemiptera: Aphididae) on Different Pear Cultivars With Discussion on Curve Fitting in Life Table Studies

Abstract: Population growth parameters of the Dysaphis pyri (Boyer de Fonscolombe) (Hemiptera: Aphididae) were evaluated on four different cultivars (Coscia, Ankara, Williams, and Santa-Maria) of pear (Pyrus communis L.) under field conditions in the Van region of Turkey. Aphids were kept on leaves of 10-yr-old pear trees in Plexiglas clip-cells (20 mm in diameter and 10 mm in height, with the upper side covered with muslin). For the description of the stage differentiation during population growth, we analyzed raw data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The parameters of life tables often vary with temperature, chemical pesticides and host species [ 36 , 37 , 38 , 39 , 40 , 41 ]. The r summarizes the physiological qualities of an animal relative to its capacity of increase and is often used to compare the fitness of populations across diverse climatic and food-related conditions [ 25 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of life tables often vary with temperature, chemical pesticides and host species [ 36 , 37 , 38 , 39 , 40 , 41 ]. The r summarizes the physiological qualities of an animal relative to its capacity of increase and is often used to compare the fitness of populations across diverse climatic and food-related conditions [ 25 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing awareness among the growers about advantage of integrated pest management and eco‐friendly insect pest management, studies on life table of important key pests like T. absoluta and their implication in designing newer advanced management strategies are certainly and urgently needed. Population growth parameters of a cohort on various hosts in controlled conditions are useful to asses the biotic potential of an insect facing a new host and to evaluate quality of the host plant (Atlihan et al, ; Pereyra & Sánchez, ) because the insect pest growth rate can be estimated accurately using these parameters. The population growth parameters of T. absoluta on tomato, potato, and eggplant were calculated employing the age‐stage, two‐sex life table which gives accurate as well as more realistic life table because it is capable of describing the differentiation among stages and allows the incorporation of dynamic developmental rates among individuals (Atlihan & Chi, ; Huang & Chi, ; Özgökçe, Chi, Atlihan, & Kara, ; Qayyum, Aziz, Iftikhar, Hafeez, & Atlihan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Food quality and quantity directly or indirectly affect development, survival, and fecundity of insects, and consequently influences population fitness (Atlihan, Kasap, Özgökçe, Polat Akköprü, & Chi, ; Özgökçe & Atlihan, ; Özgökçe, Chi, Atlihan, & Kara; Polat‐Akköprü, Atlihan, Okut, & Chi, ; Scriber & Slansky, ; Slansky, ). Hence, understanding population growth performance of pests on other crops is necessary for developing effective control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study indicated that host-plant nutrition influenced the parasitoids indirectly and among the 24 tested treatments, the longest larval, and pre-adult durations as well as the lowest, R 0 , T, λ, and r values belonged to E and R, indicating that this cultivar is partially unsuitable or tolerant; however, K and SB seemed to be favorable for development of herbivores and wasps. In fact, the lower (r) and (λ) values observed in the present study can mainly be attributed to the longer pre-adult developmental time, lower fecundity, lower survival rates, and delayed peaks in reproduction (Atlihan et al 2017). Efficiency of wasps declined when herbivores fed on poor nitrogen host plant (Winter and Rostas 2010) and application of fertilizers enhanced the development rate of the parasitoid (Garratt et al 2010).…”
Section: Resultsmentioning
confidence: 45%